Accelerating Structural Transformation through IKN : An Analysis Study of the Formation of a New Economic Base and Its Impact on Indonesia's Competitiveness - RM Bramastyo KN; Enny Istanti (International Forum of Researchers and Lecturers, 2024)
Structural transformation is an important process in the economic development of a country. In Indonesia, the plan to move the National Capital City (IKN) from Jakarta to Nusantara in East Kalimantan is one of the strategic steps in accelerating structural transformationThe methodology used in this study is a qualitative and quantitative approach. The results of the study show that the acceleration of structural transformation through the development of IKN has a significant impact on the formation of a new economic base and increasing Indonesia's competitiveness. The formation of a new economic base in IKN can be seen from the emergence of technology and innovation-based industrial clusters. The impact on national competitiveness can be seen from the increase in productivity and innovation capacityThe analysis of the acceleration of structural transformation through the development of the IKN shows a fundamental change in Indonesia's economic base. The development of IKN as a smart forest city accelerates structural transformation through three main mechanisms. The impact on the formation of a new economic base can be seen from the shift in the economic structure in the IKN area and its surroundings. Structural transformation is also reflected in changes in the composition of the workforce and investment patterns. The impact analysis on Indonesia's competitiveness shows a significant increase in several dimensions